Formation of Three Selected AGEs and their Corresponding Intermediates in Aldose‐ and Ketose‐lysine Systems. Issue 3 (14th May 2020) - Xue, Chaoyi; Shi, Zhenhua; He, Zhiyong; Wang, Zhaojun; Qin, Fang; Chen, Jie; Zeng, Maomao
Abstract : Advanced Glycation End Products (AGEs) could be formed with α ‐dicarbonyl compounds as intermediates; however, simultaneous determination of AGES as well as their precursors and intermediates have rarely been mentioned, so as to investigate the reaction. In this work, lysine was reacted with aldoses (galactose, glucose) and ketoses (fructose, sorbose) to investigate the effects of sugar type and heating temperature. Two high‐performance liquid chromatography‐tandem mass spectrometry methods were developed to quantify AGEs and the corresponding α ‐dicarbonyl compounds. The results demonstrated that aldoses were more prone to form intermediates and final products than ketoses from the point of view of absorbance (at 294 and 420 nm). Aldose systems were prone to form glyoxal, whereas ketose systems tended to generate methylglyoxal and 3‐deoxyglucosone. The relative reaction activity of sugars in forming N ε ‐carboxymethyl‐lysine depended upon heating temperature for aldose and ketose systems. The aldose was more liable to generate N ε ‐Carboxyethyl‐lysine (CEL) than ketose, with the CEL generation for each sugar occurred in the order galactose > glucose > sorbose > fructose. The obvious differences between different types of sugars suggest that further research is needed on the degradation of sugars to form intermediates and on the reaction of α ‐dicarbonyl to generate AGEs. GRAPHICAL ABSTRACT: